Venlafaxine Hydrochloride Granules Using Natural Polymers as Multiparticulate Drug Delivery System - B & Jyosna Doniparthi, Dr. Jeevana Jyothi (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The present investigation endeavors the importance of natural polymers for the sustained oral drug delivery. In an attempt to weigh up the efficiency of natural polymers in sustained oral delivery, an antidepressant venlafaxine hydrochloride, a highly water-soluble drug was selected as a challenging model. Materials and Methods: Different formulations (F1-F12) were prepared using drug, xanthan gum (XG), guar gum (GG) at 1:1, 1:2, and 1:3 ratios, and different polymer blends of chitosan, XG, and GG at 1:1, 1:4, and 4:1 ratios. Multiparticulates (granules) were prepared using wet granulation method and then were filled into empty hard gelatin capsules. The prepared multiparticulate drug delivery systems (MDDS) were characterized for drug-excipient compatibility study, physical evaluation, and in vitro drug release. Results and Discussions: Fourier-transform infrared spectroscopy study confirmed the absence of chemical interactions between drug and polymers. Differential scanning calorimetry analysis indicated the uniform dispersion of drug in the matrix. The physical and flow properties of the granules and MDDS were evaluated and found to be within the acceptable limits. The in vitro drug release study of the optimized formulation (F8) sustains the release of drug to 85.3% at the end of 20 h, while Venlor XR sustains the release of drug to 97.35% at the end of 12 h. Kinetic analysis of dissolution data indicated that the drug release follows first-order kinetics through Quasi-Fickian diffusion. Conclusion: It can be concluded from the study that the prepared MDDS using polymer blend of chitosan with XG at 1:4 ratio are the versatile release retardant material, which could release the drug for 20 h.